Pengembangan Sistem Informasi Prestasi Siswa Dinas Pendidikan Kota Malang Berbasis Website - Charisma Ubaidah Cholilia; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Database system for recording student achievement in Education Office of Malang is still constrained and is not efficient. Data collection cannot be done optimally because data collection is still semi-automatic. Of course this has limitations, and have an impact on the timing of submitting student performance reports that are not real-time, unavailable presentation of student achievement data that is easily accessible, and storage of disorganized achievement data. Unorganized data storage makes employees was constrained in finding data and can risk losing data. With the existence of these problems, it is necessary to have a system that can help the process of collecting student achievement. The research on the development of Student Achievement Information Systems (SIMPRES) was conducted to help Malang City Education Agency in collecting student achievement data. System development is done using the waterfall method. Then to ensure that the system is in accordance with user requirements, the system is tested using validation testing, compatibility testing, and usability testing methods. The results of this system test are valid in testing validation testing, compatible with all browsers through compatibility testing, and obtain 81 in grade B through usability testing which means the system is easy to use by the user.